Diversified Synthesis of Novel Quinoline and Dibenzo Thiazepine Derivatives Using Known Active Intermediates - Sharada, L.N.; Satyanarayana Reddy, G.S.; Sammaiah, B.; Sumalatha, D. (Asian Journal of Chemistry, 2013)
The novel drug development to control resisting infections in conventional drug therapy is a need of today. Few antiulcer relative derivatives developed by approaching convergent synthesis. The derivatives synthesized successfully are dibenzo thiazepine-pyridine (SLN11-SLN15) and benzimidazole-hydroquinoline based derivatives (SLN16-SLN20). It involved the coupling through microwave, sonication and conventional techniques at final step. The efficient technology identified as sonication technique basically time and yield. The reported compounds were structural characterized by elemental analysis and spectral studies such as 1H, 13C NMR and MS.